Mathematical Analysis of an Obesity Model with Eating Behaviors (CSIAM Transactions on Applied Mathematics, 2020)
Overweight is a social disease, which is transmitted through social networks. A mathematical model is proposed to simulate the dynamics of social obesity,where the structures of individual heterogeneity and overeating behaviors are incorporated. The basic reproduction number of the disease is calculated and is shown tobe a threshold for disease invasion. Sufficient conditions for the global stability of anendemic equilibrium is established by Lyapunov functions. Numerical simulationsare provided to reveal how interventions through treatment to eating behaviors andeducation to susceptible individuals suppress the progression of the disease.